(untitled) (Medico Legal Update, 2020)
Objective: The present study aimed to knowing weak points which is lead to negligence it could be transmission of nosocomial infection. Material and Method: The sample of the study included 100 nurses were selected randomly from the pediatric, surgical, emergency, I.C.U and operation room departments in AL-Salam and AL-Jamhory Teaching Hospitals in the Mosul City during a period which extended from the 1/10/2018 to 20/1/2019, the data were collected through an observation of each subject of the sample during working with the patients and fulfill in the checklist sheet. Result: The findings of this research revealed significant values between gender and personal hygiene practices to the advantage of female, also there is significant relationship between level of education and personal hygiene practices to the advantage of colligate nurses. Conclusion: the present study demonstrated that there was negligence in some personal hygiene practices among nurses such as (hand washing, use protective devices, use protective measures, and hepatitis B vaccination).